Recycled Aggregate Concretes (RACs) for Structural Use: An Evaluation on Elasticity Modulus and Energy Capacities - Dilbas, H.; Cakir, O.; Simsek, M. (SPRINGER, 2017)
The determination of the parameters of concrete (i.e., elasticity modulus and tensile strength) is a crucial task in material engineering. For this purpose, structural codes propose some empirical formulas to estimate the parameters of materials and are useful for designers rather than the experimental process. However, the estimated results usually vary for different standards. Hence, this research paper aims to compare the elasticity modulus formulas considering six standards (TS 500, ACI 318M-05, CSA A23.3-04, SP 52-101-2003, EN 1992-1-1 and AS-3600-2001) with experimental elasticity modulus test results. The results demonstrate that the TS 500 and EN-1992-1-1 overestimate the elasticity modulus and the SP-52-101-2003 estimates are closely aligned to the experimental results. In addition, a new equation for modulus of elasticity including the compressive strength and the density is derived for RAC. Also, energy capacities of concretes (elastic energy capacity, plastic energy capacity and toughness) are evaluated considering compressive strength test data. According to energy capacities of concretes, the proportions of 5 % silica fume (SF) and 30 % recycled aggregate (RA) are proposed as the optimum ratio.
Keywords: Elasticity modulus; Standards; Energy capacities; Silica fume; Recycled aggregate; SELF-COMPACTING CONCRETE; HIGH-STRENGTH CONCRETE; MECHANICAL-PROPERTIES; COMPRESSIVE STRENGTH; HARDENED PROPERTIES; COARSE AGGREGATE; Engineering